2017
DOI: 10.1124/dmd.117.078949
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Unstirred Water Layer and Hepatocyte Membrane Integrity In Vitro for Quantification of Intrinsic Metabolic Clearance

Abstract: Prediction of clearance-a vital component of drug discovery-remains in need of improvement and, in particular, requires more incisive assessment of mechanistic methodology in vitro, according to a number of recent reports. Although isolated hepatocytes have become an irreplaceable standard system for the measurement of intrinsic hepatic clearance mediated by active uptake transport and metabolism, the lack of prediction reliability appears to reflect a lack of methodological validation, especially for highly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…Studies often involve hepatocyte uptake studies over a range of drug concentrations to be able to estimate V max and K m parameters, allowing active versus passive permeability to be determined, studies at 4°C or in inactivated/dead hepatocytes to differentiate unspecified binding effects, microsome studies to estimate metabolic clearance, sandwich-cultured hepatocytes to differentiate biliary clearance from metabolic clearance, and attempts to predict efflux permeability clearances by subtracting metabolic and biliary clearances from total cellular clearance measures. Layered on top of the experimental difficulties in carrying out such studies is the recognition that in vitro to in vivo extrapolation is unreliable with in vitro measures predominantly and often significantly under-predicting in vivo clearance even when only metabolism is evaluated as we and others have well documented (3740). For example, in the Yao et al (27) cerivastatin-cyclosporine DDI analysis the in vitro value for fraction of cerivastatin metabolized by CYP2C8 was found to be too low to account for the observed clinical data.…”
Section: Resultsmentioning
confidence: 99%
“…Studies often involve hepatocyte uptake studies over a range of drug concentrations to be able to estimate V max and K m parameters, allowing active versus passive permeability to be determined, studies at 4°C or in inactivated/dead hepatocytes to differentiate unspecified binding effects, microsome studies to estimate metabolic clearance, sandwich-cultured hepatocytes to differentiate biliary clearance from metabolic clearance, and attempts to predict efflux permeability clearances by subtracting metabolic and biliary clearances from total cellular clearance measures. Layered on top of the experimental difficulties in carrying out such studies is the recognition that in vitro to in vivo extrapolation is unreliable with in vitro measures predominantly and often significantly under-predicting in vivo clearance even when only metabolism is evaluated as we and others have well documented (3740). For example, in the Yao et al (27) cerivastatin-cyclosporine DDI analysis the in vitro value for fraction of cerivastatin metabolized by CYP2C8 was found to be too low to account for the observed clinical data.…”
Section: Resultsmentioning
confidence: 99%
“…It has become clear in recent years that physiologic scaling of CL int obtained from suspended human hepatocytes not only underpredicts in vivo CL int on average (Ito and Houston, 2005;Riley et al, 2005;TABLE 2 Accuracy and precision of human hepatocyte prediction of in vivo CL int using rat and human in vitro-in vivo scaling factors, as represented by GMFE, RMSE, and the percentage of predictions that fall within 2-fold of the observed in vivo CL int Segregated Hepatocyte Scaling Factors in Prediction of Clearance Brown et al, 2007;Bowman and Benet, 2016) but does so in a clearance-dependent way (Hallifax et al, 2010;Wood et al, 2017). Although the reasons for this dependence remain unclear but could involve effects of the unstirred water layer and/or cofactor depletion in vitro (Hengstler et al, 2000;Hewitt et al, 2000;Hewitt and Utesch, 2004;Hallifax et al, 2010;Foster et al, 2011;Wood et al, 2017Wood et al, , 2018, achieving resolution of this clearance-dependent bias from the considerable prediction uncertainty has provided an opportunity to apply better targeted empirical correction. Because prediction from rat hepatocytes has now been shown to be clearance dependent in the same manner as human hepatocytes (Wood et al, 2017), there appears to exist a basis for renewed potential in the utility of rat hepatocytes for prediction of human in vivo CL int .…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the system-specific factor, there are species differences between hepatocytes whose impact can be dependent on the drug, such as the shaking of hepatocyte incubations (Wood et al, 2018). Other drugspecific species differences in hepatic clearance include metabolic and transporter pathways, not least due to species differences in cytochrome P450 enzymes or transporters resulting in differences in capacity and/or affinity.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…The sources of inaccuracies are still poorly understood [3][4][5]. Dissimilar biological and methodological factors are cited frequently as causes [6,7], and efforts are underway to identify and reduce IVIVE inaccuracies. For example, reported that, for low-clearance compounds, errors in determining the unbound fraction of drug are proportional to the errors in predicted clearance [8].…”
Section: Introductionmentioning
confidence: 99%